2022
DOI: 10.1093/jas/skac055
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and genetic correlation estimates of semen production traits with litter traits and pork production traits in purebred Duroc pigs

Abstract: We estimated heritabilities of semen production traits and their genetic correlations with litter traits and pork production traits in purebred Duroc pigs. Semen production traits were semen volume, sperm concentration, proportion of morphologically normal sperms, total number of sperm, and total number of morphologically normal sperm. Litter traits at farrowing were total number born, number born alive, number stillborn, total litter weight at birth, mean litter weight at birth, and piglet survival rate at bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(40 citation statements)
references
References 71 publications
(111 reference statements)
2
33
5
Order By: Relevance
“…Indirect estimation could be useful when the initial value setting for REML iteration or direct REML estimation did not converge. For example, Ogawa et al (2022) reported the indirectly estimated value of the genetic correlation between survival rate at birth and survival rate from birth to weaning in pigs because it could not be directly estimated. On the other hand, indirect estimates obtained using other estimates could deviate from the true value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect estimation could be useful when the initial value setting for REML iteration or direct REML estimation did not converge. For example, Ogawa et al (2022) reported the indirectly estimated value of the genetic correlation between survival rate at birth and survival rate from birth to weaning in pigs because it could not be directly estimated. On the other hand, indirect estimates obtained using other estimates could deviate from the true value.…”
Section: Resultsmentioning
confidence: 99%
“…Production efficiency in livestock production, including average daily gain, residual feed intake, and survival rate at birth (e.g., Homma et al, 2021; Ogawa et al, 2022; Yazaki et al, 2020), can be defined as the difference and ratio. For superovulatory response traits in dairy cattle, König et al (2007) estimated genetic parameters of ratio traits, such as the percentage of transferable embryos; such analyses were not performed in Zoda et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, an upper bound for thr was set to 25.0°C because the maximum value of expected T was estimated to be 26.3°C, and that for per was 50 according to the upper bound for ADG of 1500 g from 30 to 105 kg in this study (i.e., 75,000/1500 = 50). Note that the length of testing period (days from 30 to 105 kg) was different among animals, that the effect of heat stress could be more serious for heavier pigs (Katsumata et al, 1996 ; Quiniou et al, 2000 ) and that the definition of ADG and rearing conditions could be different among the studies (e.g., Homma et al, 2021 ; Ogawa, Kimata, et al, 2022 ; Yazaki et al, 2020 ). Therefore, a more sophisticated study to identify a suitable indicator of cumulative heat load and its impact on growth performance in pigs should be performed.…”
Section: Resultsmentioning
confidence: 99%
“…Studies to identify indicators of heat stress (e.g., Cross et al, 2018 ; Gourdine et al, 2019 ; Poullet et al, 2022 ) and those for predicting breeding values for heat tolerance using public weather data (e.g., Tiezzi et al, 2020 ; Usala et al, 2021 ; Zumbach et al, 2008 ) have also been performed. Thus, developing methodology to genetically improve pigs to cope with climate change would be valuable (e.g., Gourdine et al, 2021 ; Hara et al, 2022 ; Ogawa, Kimata, et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation